Precipitation as a factor triggering landslide activity in the Kamień massif (Beskid Niski Mts, Western Carpathians) - Papciak, Tomasz; Malik, Ireneusz; Krzemień, Kazimierz; Wistuba, Małgorzata; Gorczyca, Elżbieta; Wrońska-Wałach, Dominika; Sobucki, Mateusz (Bulletin of Geography. Physical Geography Series, 2015)
On the landslide slope in the Beskid Niski Mts (Western Carpathians) 48 silver firs were cored for dendrochronological samples. Tree-ring widths were measured for the upslope and downslope sides of each stem. Events of landslide activity were dated using the method of the eccentricity index. The tree-ring record of landsliding was compared with the occurrence of precipitation in the study area. The nature of the relation between precipitation and landsliding is complex. We have found a statistically significant correlation between landsliding and the number of days with 24-hour precipitation totals above 20 mm and high 3-, 5-, and 10-day precipitation totals during winter half-years. Thus landsliding in the Kamień massif is triggered mainly by high precipitation totals in the preceding winter period. No such relation was found for annual precipitation totals and different types of precipitation totals in the summer period. Single landsliding events related to high summer precipitation totals were found, but the correlation is not statistically significant. In addition some landsliding events are 1–2 years lagged after the occurrence of high long-term precipitation totals. It seems that the strongest landsliding events resulted from sequences of wet summer, wet winter and once again wet summer seasons directly following one another.